The ecological interaction between habitat composition, habitat quality and abundance of some wild ungulates in India - Mathur, V (1991)
The ecological interrelationships between the habitat composition, habitat quality and abundance of three wild ungulate species, viz. Chital (Axis axis), Sambar (Cervus unicolor) and Nilgai (Boselaphus tragocamelus) were investigated in three National Parks in India. The study sites differ in the structure and composition of the habitat and also occur along a rainfall gradient. The study incorporates a new approach of using forest compartments for gathering baseline ecological data. The significance of these compartments in serving as ecological bench-marks for monitoring habitat condition has been demonstrated. Toe-point transect, a modification of the point-intercept method has been extensively used to obtain rapid, reliable but coarse ecological data on ground and aerial cover and the results obtained are compared with those from the visual estimation method. Motorcycle and foot-based line transects have been used to obtain data on animal abundance. The significance of the results indicating that motorcycle transects are an efficient and reliable means of estimating the abundance of Chital and Nilgai, while foot transects provide more reliable estimates of Sambar abundance is discussed. Data on 22 habitat variables were gathered in the summer and winter seasons from all the study sites and were statistically analysed using Generalized Linear Interactive Modelling (GLIM) procedures. The habitat requirements of the three ungulate species have been determined, which enhance our understanding of the complex herbivore-habitat relationships. Analyses of habitat selection, central to the understanding of animal ecology, has been done to understand the mechanisms which permit species to co-exist. The results indicate that the three species are ecologically separated and that resource partitioning is achieved primarily by habitat partitioning. Sambar, a forest ungulate, largely occurs in the forest-woodland habitats; Chital, a species of the habitat 'edge', occurs in the woodland-grassland habitats while Nilgai prefers the miscellaneousopen and grassland habitats. The three ungulate species together contribute more than 78% to the total wild ungulate biomass. This is presumably because these species are by nature generalist and are able to exploit the unpredictable resources more efficiently than specialist species. The differential biomass/rainfall relationships of three species observed in the study have been explained on the basis of habitat requirements and feeding strategies adopted by these species. The ecological biogeography of the three ungulate species has been discussed and their ecological equivalents in Africa have been examined. The significance of above in enhancing our understanding of evolutionary biology is discussed. The study has shown that habitat composition is an all-important factor in large herbivore biology and that animal density may be used as an indicator of habitat quality.